The Influence Of Word Of Mouth, Location And Price Perception On Purchasing Decisions (Survey Of Cilok Golden Tasikmalaya Consumers): - Aprizha, Wynne Zaskhia; Pauzy, Depy Muhamad; Asyiah, Ai Kusmiati (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This research aims to determine the influence of word of mouth, location, and price perception on purchasing decisions in Cilok Golden Tasikmalaya. The method used in this research is descriptive analysis using a survey approach. With a research sample of 100 Cilok Golden Tasikmalaya consumers. The data collection used was a questionnaire. The analytical tool used in this research is multiple linear regression using SPSS 25.0. The results show that simultaneously the variables used in this research, namely word of mouth, location, and price perception, have a significant influence on purchasing decisions at Cilok Golden Tasikmalaya. Likewise, partially there is a significant influence of word of mouth on purchasing decisions at Cilok Golden Tasikmalaya, location also partially influences purchasing decisions at Cilok Golden Tasikmalaya, and partially there is a significant influence of price perception on purchasing decisions at Cilok Golden Tasikmalaya.